2002
DOI: 10.1002/cncr.10454
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary melanoma revisited

Abstract: BACKGROUND Incidence of cutaneous melanoma continues to increase in the Caucasian population worldwide. Approximately 5% of melanoma patients develop additional primary melanoma. This rate is significantly higher than the estimated lifetime risk of an individual for developing the disease (1.4%). These features suggest that a genetic predisposition may underlie multiple primary melanomas (MPMs). Prior studies had identified CDKN2A mutations in a few MPM individuals. The objectives of this study were to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 33 publications
(39 reference statements)
6
65
1
Order By: Relevance
“…34 It has been estimated that germline mutations in CDKN2A occur in 8.3% to 15% of patients with MPM. 10,34,35 In a population-based, case-control study, Berwick et al reported a relative risk of 4.3 for a functionally relevant mutation in CDKN2A in patients with MPM versus patients with SPM. 36 Furthermore, allelic variants of melanocortin-1-receptor (MC1R) may modify the penetrance of CDKN2A mutations and have been observed at an increased frequency in patients with MPM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 It has been estimated that germline mutations in CDKN2A occur in 8.3% to 15% of patients with MPM. 10,34,35 In a population-based, case-control study, Berwick et al reported a relative risk of 4.3 for a functionally relevant mutation in CDKN2A in patients with MPM versus patients with SPM. 36 Furthermore, allelic variants of melanocortin-1-receptor (MC1R) may modify the penetrance of CDKN2A mutations and have been observed at an increased frequency in patients with MPM.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Various single-center and population-based studies have reported that between 1.2% and 8.6% of patients who have a history of melanoma will develop subsequent melanomas. [3][4][5][6][7][8][9][10][11][12] Several risk factors for the development of more than 1 primary melanoma have been established, the most important of which include a family history of melanoma and a personal history of dysplastic nevi. 10,[12][13][14] The initial melanoma in patients who have multiple primary melanomas (MPM) usually is the thickest of the melanomas that eventually develop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of these malignancies in the world was 54.41% for BCC,grow slowly and does not metastasize to the bloodstream (Schatton et al, 2008), while SCC tumors are metastatic, aggressive and fatal. Malignant melanoma (MM) is an aggressive tumor that its occurrence has increased rapidly during the past two decades (Blackwood et al, 2002;Gyrylova et al, 2014). The incidence rate of melanoma has been reported to be correlated with age, socioeconomic status, tumor localization (Jemal et al, 2011), and gender (Gyrylova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of risk of multiple primary melanomas have been concerned mainly with influences of the previous history of melanoma, presence of dysplastic nevi, or possible genetic susceptibility [2][3][4]. While sun exposure is recognized as the major cause of melanoma in populations of European origin [5], studies of sun exposure and melanoma so far published have compared sun exposure in people with a first melanoma, or any melanoma, with that in people who have not had a melanoma.…”
Section: Introductionmentioning
confidence: 99%